Discourse variation of vague language: vague quantifiers in spoken and written Lithuanian - Ruzaitė, Jūratė (Taikomoji kalbotyra, 2018)
Vagueness is a controversial issue, which was long stigmatised by both researchers and laypeople and largely neglected in linguistics until the publication of Channell’s (1994) study, which demonstrated that vague language (VL) is a multi-faceted phenomenon of high pragmatic importance. The present study focuses on one of the most central categories of VL in Lithuanian, i.e. vague quantifiers, which can be defined as non-numerical expressions used for referring to quantities, e.g. daug (“a lot”), mažai (“little/few”), keletas (“several”), or šiek tiek (“a little bit”). The meaning of quantifiers frequently encodes some evaluative content concerning the significance of a quantity. The evaluative function is an important and intended speaker’s message, expressed by choosing a vague expression, and is lost if reformulated into a precise expression. A systematic account of this pragmatic category has not been carried out yet in Lithuanian, and the vast majority of research on vague quantifiers focuses mainly on English with only very few exceptions.   VL is omnipresent and is used in all discourse types, but to a different extent and for different purposes; therefore, this investigation has a two-fold aim: (a) to determine the distribution of quantifiers in different discourses including spoken interaction and a variety of written texts (i.e. academic texts, newspapers and magazines, publicist texts, administrative texts, and fiction); and (b) to overview when and why vague quantifiers are prioritized over precise numerical references.The data for this investigation has been obtained from the Corpus of the Contemporary Lithuanian Language (tekstynas.vdu.lt), which is a reference corpus comprising over 140 mln words; it represents five major discourse types analysed in this paper. The present analysis has been carried out within the framework of corpus linguistics, pragmatics, variationist sociolinguistics, and discourse analysis; it is primarily quantitative, but to explain some dominant tendencies in the results, it also deals with some qualitative aspects.The findings obtained from spoken and written discourse have revealed that quantifiers are distributed very unevenly in the two modes of language; the results have also shown some dramatic differences in the use of quantifiers in different written texts. Their distribution and functions depend on the formality of quantifiers and their semantic type. Multal quantifiers (i.e. those referring to large quantities) are emphatic, whereas paucal quantifiers (i.e. those referring to small quantities) are mainly used for mitigation and are more prone to soften the effect of negatively loaded lexemes. Importantly, quantifiers are used for persuasion since they evaluate a quantity and convey the speaker’s interpretation of its significance. They can be important in discourse structuring, in shaping interpersonal relationships, and as a face-saving strategy. Due to the large variety of communicative functions that quantifiers can perform, they are an important category in second language teaching and should be adequately dealt with in lexicography.
Keywords: vague language; quantifiers; spoken and written discourse; corpus; multal and paucal quantifiers; functions